La recomendación de la OMPI para la protección del patrimonio inmaterial de la nación frente al fenómeno transfronterizo de la biopiratería (2017)
This paper aims to expose the topic of Biopiracy, known as practice, which is decreed in the misappropriation of biodiversity and traditional knowledge and entails the biological, intellectual, cultural and economic impoverishment of the various mega countries. The main objective of this paper is to demonstrate the importance of protecting traditional knowledge and the intangible heritage of the nation by identifying the role of national and international legislation in trade, intellectual property, natural diversity and traditional practices. Indigenous communities and their control. Through experiences shared by other countries, through the implementation of competent international bodies in national jurisdictions such as WIPO and the suggestion of adoption of its recommendation, which could also be implemented in Colombian legislation to Face and cancel this phenomenon.